EXPERIMENTAL COMPARISON OF DIFFERENTIAL-PHASE METHOD AND METHOD OF DYNAMIC FOCUSING IN DEFINING OF ROUGHNESS PARAMETERS OF SURFACES - Kunce, K.; Modler, N.; Stelmakh, O.; Sofronov, O.; Dugan, V. (Science-based technologies, 2011)
In this work you can find information about differential-phase method and method of autofocusing, which are used on differential-phase laser scanning profilograph-profilometer (DFLSPP) and microscope «MICROSCAN» correspondently. Also is considered experimental comparison of defining of 3D micro- and nano-geometrical surface conditions and standardized roughness parameters of surface with the help of those methods.